MENGENAL MEDIA PENDIDIKAN DAN PERANNYA DALAM PEMBELAJARAN - Nurhayani; Ismail Syakban (JIP: Jurnal Ilmu Pendidikan, 2026)
Educational media is a crucial component in the learning process, serving as a means of conveying messages from educators to students. This research aims to examine the concept of educational media and its role in increasing learning effectiveness. The research method employed is a qualitative approach, utilizing literature studies through the review of various books and scientific articles relevant to the topic of learning media. The data was analyzed using content analysis techniques to identify the role, types, and benefits of educational media in the teaching and learning process. The results of the study indicate that the effective use of educational media can enhance students' material understanding, learning motivation, and active involvement. Additionally, the development of digital media offers opportunities for more interactive, flexible, and student-centered learning. However, the effectiveness of educational media is highly dependent on educators' ability to choose and utilize it effectively in accordance with learning objectives and the characteristics of students. Thus, educational media must be strategically integrated into learning plans to enhance the quality of education